Multifocal Keratitis in 23-year-old Woman with β-Thalassemia - Asti, Annisa Kinanti; Zuhria, Ismi (Universitas Airlangga, 2025)
Introduction: Multifocal keratitis can result from infectious and non-infectious causes, and its etiology is often challenging to pinpoint. Ocular complications are common in β-thalassemia and can have serious consequences. This case highlights an unusual presentation of multifocal keratitis in a patient with β-thalassemia. Case Presentation: A 23-year-old woman with β-thalassemia, diagnosed 12 years ago, was referred by a hematologist for pain in her right eye persisting for the past two weeks. She reported redness, tearing, and light sensitivity. Six months prior, she experienced similar symptoms, which had left a white spot in her right eye. Recently, this spot had multiplied and spread across the ocular surface. Visual acuity (VA) was 6/40 in the right eye on examination. Findings included palpebral spasm, conjunctival and pericorneal injection, and multiple infiltrates on the anterior corneal surface. Fluorescein staining was positive for numerous infiltrates. Schirmer and break-up time (BUT) tests indicated an unstable tear film. Treatment included antibiotic eye ointment, preservative-free artificial tears, mucous membrane pemphigoid (MMPs) inhibitors, and oral ascorbic acid. Two weeks later, VA improved to 6/9, with a reduction in infiltrates and fluorescein staining. Conclusion: Prompt management is essential for preserving vision and preventing complications in ocular surface diseases while diagnostic procedures are underway.